Commenting online - attitudes and habits of Serbian citizens - Neda; Milosavljević, Ilija (Sociološki pregled, 2022)
Online commenting has, at first glance, enabled the revival of the public sphere in which practically every man has the opportunity to have his voice heard. However, practical problems and specifics of this type of public communication indicate that commenting online is significantly different from the initially predominant idealistic assumptions. The aim of this paper is to investigate how and to what extent Internet users in Serbia are involved in online commenting, why and how they see the impact and significance of this phenomenon as a whole. The research was conducted by means of a questionnaire completed by 225 respondents. The results were analyzed by descriptive and comparative statistical methods and indicate that less than a half of the citizens do comment online, that most of them do not think it is possible to change other people’s opinions in this manner, but they still consider it important and influential. Certain differences have also been observed in relation to the respondents’ age and level of education.